Bolivia en el mundo: Sus relaciones económicas internacionales - Juan Antonio Morales (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2006)
En este trabajo se examina las nuevas condiciones para las relaciones económicas internacionales de Bolivia que ha creado el gobierno del Movimiento al Socialismo (MAS). La visión más común en los gobiernos anteriores a los del MAS era que si Bolivia ha de desarrollarse, necesitaba participar ampliamente en el comercio internacional y atraer, al mismo tiempo, flujos de capital externo para financiar las inversiones requeridas para su crecimiento. Se veía a la participación en la globalización como una condición necesaria mas, obviamente, no suficiente para el crecimiento y el desarrollo. La posición del gobierno del MAS difiere en muchos aspectos de la concepción anterior y de las visiones de los gobiernos previos. Ella está claramente más volcada al interior, con un papel más importante para el estado y en pos de una mayor industrialización de los recursos naturales del país, siguiendo modelos de mediados del siglo pasado. Las preguntas que hay que responder son: cuál es el espacio de maniobra del gobierno del MAS dadas las tendencias de los principales socios comerciales de Bolivia y de las fuentes internacionales de financiamiento? Cuán bien preparada está la economía boliviana para actuar bajo otras reglas de juego? Qué consecuencias puede tener el retorno de políticas arcaicas? – – The “deliberative development” approach to policy reform has gained popularity in both academic and policy circles without a clear understanding of the requirements for its success. Based on a reading of the deliberative democracy literature, we detail those requirements, finding them to be quite restrictive. We then examine Bolivia's 2000 National Dialogue, a national deliberation on development policy, and find—not surprisingly—that these requirements were generally missing. More importantly, we demonstrate that the lack of these requirements is not benign: the institutional characteristics of the Dialogue had direct effects, and the Dialogue continues to affect Bolivia's politics in debatable ways. The late 1990s and early part of this decade witnessed what appeared to be a major change in the approach of international development institutions to policy reform. The most important evidence of this change was the Poverty Reduction Strategy Paper (PRSP) initiative of the World Bank and International Monetary Fund. This initiative, which arose in 1999 in the context of updating the Heavily Indebted Poor Countries' (HIPC) Initiative, required countries to prepare a PRSP prior to receiving debt relief (see International Monetary Fund and International Development Association, 1999). Each country's PRSP was to outline an overall strategy to reduce poverty, including structural reforms such as trade and privatization as well as specific anti-poverty programs. These PRSPs are now required to receive any World Bank or IMF concessional assistance. What made the PRSP initiative particularly innovative and noteworthy was that the Bank and Fund required that the strategy be developed in a “participatory” way. That is, the PRSP needed to be based on some sort of consultative process by which the government solicited input from various societal groups—including local nongovernmental organizations (NGOs), businesses, and unions—and then incorporated those preferences in the policy. This approach to government policymaking seemed to go directly against a line of academic work on economic reform that had been influential in these institutions for years (e.g. Sturzenneger and Tommasi, 1998), arguing that there was an inverse relationship between the success of economic reform and the amount of participation of society in making policies. Having criticized this old approach for years, most NGOs and developing country governments supported the new direction taken by the World Bank and IMF. In fact, few critics of the approach (e.g. Stewart and Wang, 2003) have critiqued the idea of participation, most instead focusing their critiques on the poor “extent” and “quality” of participation. In one of the benchmark articles supporting this “deliberative” approach to policy reform, Peter Evans (2004) notes that such an approach to policymaking is supported by work by the economists Amartya Sen (1999) and Dani Rodrik (2000), who argue that participation and public deliberation are means to better policies. Evans writes, “If it were possible to implant this sort of deliberative process in political units large enough to impact developmental trajectories—say, the provincial or municipal level—we would have something that could be called `deliberative development'” (2004: 37). Discussing examples from Porto Alegre, Brazil, and Kerala, India, Evans goes on to argue that this type of development is not only desirable, but attainable. Despite its increasing popularity in the academic and policy worlds, we still know little about what is needed for the deliberative development approach to be successful. While it may be true that political processes in Porto Alegre, Kerala, and elsewhere have exhibited deliberative aspects as well as positive development outcomes, the particular details of how the former relates to the latter remain murky. Are deliberative processes appropriate for all development decisions? Are there particular characteristics of the society that need to be present in order for deliberation to work well? Are there particular characteristics of the deliberative institutions that need to be present? Can there be any negative effects if deliberation is not done well? If the deliberative development approach is to be considered a viable and superior policymaking alternative, these questions must be answered.
Keywords: 330; Außenwirtschaft; Bolivien